Exploring the acceptability and usability of a novel social innovation to encourage physical activity: The iStep prototype. (26th September 2018) - Grindell, Cheryl; Mawson, Sue; Gerrish, Kate; Parker, Stuart; Bissell, Paul
Abstract: This study explored the acceptability and usability of the iStep prototype a novel social innovation to encourage intergenerational physical activity (PA) to help reduce obesity levels in older age. Obesity is a major public health issue and physical inactivity is one of the many factors that influence this, especially in childhood and later life. iStep (a pedometer and interactive website) sought to increase PA levels across the life course through intergenerational partnerships participating in walking challenges together. This was a qualitative mixed methods study involving 130 participants from two different settings. Pupils and teachers from a local secondary school ( n = 120) tested the iStep prototype over two separate 2‐week periods. Pupil and teacher partnerships engaged in a walking challenge using pedometers and the website platform. In addition, 10 retirement age women were involved in a modified co‐operative evaluation of the prototype. Two focus groups with pupils ( n = 9 and 20), semistructured interviews with teachers ( n = 5), and one dyadic interview (pupil/teacher) were undertaken. Data were analysed using an iterative thematic approach. Five themes were identified: perceptions of the technology, attitudes towards the walking challenge, attitudes to the intergenerational partnership, competition versus collaboration and promoting PA. The pedometer was a useful motivational tool which raised awareness of PA levels. The website was thought to be simple and easy to use. Walking was deemed inclusive and accessible to all age groups and setting a target goal was considered beneficial. Engaging in PA with a partner was regarded as a good way to provide support and encouragement. Overall, this early prototype evaluation showed that iStep has potential to be an innovative and engaging way to encourage increased PA across generations. It may positively contribute towards reducing obesity levels in older age but outcomes that effectively measure this need to be incorporated in any future iStep testing.